System and path planning algorithm for low-kV X-ray free-form surface irradiation - Rothfuß, Andreas; Bürgy, Daniel; Schneider, Frank; Wenz, Frederik; Clausen, Sven (The international journal of medical robotics and computer assisted surgery, 2018)
Objective: Intraoperative radiotherapy (IORT) after surgical resection using a low-kV-X-ray source is a proven method used in cancer treatment. However, the shape and size of the targeted surface area are limited to the size of the available applicators. This can lead to nonconformal and therefore suboptimal treatment for many patients. Methods: A system is proposed comprising an X-ray source with an applicator for surface irradiation mounted on a robotic arm. This is controlled by an algorithm designed for planning the required continuous path, enabling irradiation of any desired shape with a controlled dose distribution. Results: The system is shown to be capable of irradiating areas composed of rectangles on a flat surface with a homogeneity index of less than 7% inside the targeted area. Conclusion: The presented results demonstrate the potential of the proposed setup to eliminate the current limitations, leading to better treatment of patients.
Gesehen am 15.10.2020